Predictors and outcomes of respiratory failure among lung transplant patients with COVID‐19. Issue 3 (5th December 2021) - Lawrence, Adrian; Mahan, Luke D.; Mohanka, Manish R.; Bollineni, Srinivas; Kaza, Vaidehi; La Hoz, Ricardo M.; Zhang, Song; Kershaw, Corey D.; Terada, Lance S.; Torres, Fernando; Banga, Amit
Abstract: Background: There is limited data on the predictors and outcomes of new or worsening respiratory failure among lung transplant (LT) patients with Coronavirus disease 2019 (COVID‐19). Methods: We included all the LT patients diagnosed with COVID‐19 during a 1‐year period (March 2020 to February 2021; n  = 54; median age: 60, 20–73 years; M:F 37:17). Development of new or worsening respiratory failure (ARF) was the primary outcome variable. Results: The overall incidence of ARF was 48.1% ( n  = 26). More than 20% of patients ( n  = 11) needed intubation and mechanical ventilation. Body mass index > 25 Kg/m 2 (adjusted OR: 5.7, .99–32.93; P  = .05) and peak D‐dimer levels > .95 mcg/ml (adjusted OR: 24.99, 1.77–353.8; P  = .017) were independently associated with ARF while anticoagulation use prior to COVID‐19 was protective (adjusted OR: .024, .001–.55; P  = .02). Majority patients survived the acute illness (85.2%). Pre‐infection chronic lung allograft dysfunction (CLAD) was an independent predictor of mortality (adjusted HR: 5.03, 1.14–22.25; P  = .033). Conclusions: COVID‐19 is associated with significant morbidity and mortality among LT patients. Patients on chronic anticoagulation seem to enjoy favorable outcomes, while higher BMI and peak D‐dimer levels are associated with development of ARF. Pre‐infection CLAD is associated with an increased risk of death from COVID‐19.